The Integration of Islamic Values in Helping Students Understand Media as an Object of Study - Rabiatul Adawiah; R. Rosdiana (Manunggal Halim Jaya, 2026)
Integrating Islamic values into media learning is a strategic way to help students understand media critically, ethically, and meaningfully. Learning media not only serves as a means of conveying information but also contains messages and values that influence students' attitudes and behavior. This study aims to analyze how the integration of Islamic values can help students understand the object of media study. The method used in this study is qualitative with a descriptive approach. Data were obtained through interviews with teachers, lecturers, and students, then analyzed using thematic analysis techniques. The results revealed that the integration of Islamic values through the role of teachers in planning, implementing, modeling, and using learning media can improve understanding of the material. Students become more selective, reflective, and responsible in dealing with media, and show increased learning motivation, spiritual awareness, and character development. Thus, integrating Islamic values into media learning helps improve academic understanding while simultaneously shaping students' religious attitudes in a balanced manner in today's digital era.